Fascist Danger and the Unemployed - National Unemployed Workers Movement pamphlet, 1939 (1939)
1939 1939-1945 "Fascist Danger and the Unemployed - National Unemployed Workers Movement pamphlet, 1939" [T0153.jpg], 1939 This pamphlet, written by Wal Hannington, attacks Fascism in Germany and Italy as well as Mosley's 'Blackshirts' in Britain.